Re‐hearing parents as risks to children: Institutional listening practices in a California child welfare court - López‐Espino, Jessica (Journal of linguistic anthropology, 2024)
Building on scholarship on the politics of listening and the listening subject, this article proposes re‐hearing as a listening practice where empowered actors assert that various qualities of personhood are hearable or perceivable in relation to what marginalized persons say, do, or are otherwise associated with. Although there is an expectation that in US courts lay actors can have a hearing and a voice before the law, I identify how practices of re‐hearing shaped how parents and their narratives were heard (or left unheard) in a California child welfare court. My ethnographic research examined the listening and entextualization practices of judges, attorneys, and social workers involved in child welfare case management in California. I found that re‐hearing practices co‐constructed the continued marginalization of lay actors within contexts of state surveillance by attributing suspicion to parents and their silences in ways that exceeded and constructed evidence collected against them. Ultimately, I argue that child welfare courts and professional actors within them collectively comprise a listening institution that normalizes re‐hearing low‐income and racialized parents through frameworks of deficiency and risk. Resumen Contribuyendo a la erudición ya establecida sobre la política de la escucha y el sujeto oyente, este artículo expone el concepto de re‐oyendo como una práctica de escuchar, en la cual actores empoderados afirman que diversas cualidades de personas marginalizadas son audibles o perceptibles en relación con lo que dicen, hacen, o cómo están asociadas. Aunque se espera que en los tribunales de los EE.UU. que cualquier persona puede tener una audiencia y voz ante la ley, yo identifico que la práctica de re‐oyendo moldeó cómo padres y sus narrativas fueron escuchadas (o permanecieron sin ser escuchadas) en un tribunal de tutela y bienestar de menores en California. Mi investigación etnográfica examinó las prácticas de escucha y entextualización de jueces, abogados, y trabajadores sociales involucrados en la gestión de casos de tutela en California. Encontré que las prácticas de re‐oyendo co‐construyeron la continua marginalización de personas bajo vigilancia estatal al atribuir sospechas a los padres y sus silencios de manera que excedieron y construyeron las evidencias en su contra. Finalmente, argumento que los tribunales de tutela y bienestar de menores y sus profesionales comprenden colectivamente una institución de escucha que, a través de marcos de deficiencia y riesgo, normaliza la práctica de re‐oyendo, especialmente, a padres racializados y de bajos recursos.